Analysis of Magnetohydrodynamics Flow of Incompressible Fluids over Oscillating Bottom Surface with Heat and Mass Transfer. (1st June 2020) - Bulinda, Vincent M.; Kang'ethe, Giterere P.; Kiogora, Phineas R.
Abstract : Analysis of magnetohydrodynamics flow of incompressible fluids over an oscillating bottom surface with heat and mass transfer is discussed. The flow is free convection in nature. Momentum, energy, and concentration equations are obtained for computation of their respective profiles. The unsteady flow two-dimensional governing equations are solved numerically by the explicit finite difference method of the Forward Time Backward Space scheme. The numerical results show that the applied parameters have significant effects on the fluid flow and heat transfer and have been discussed with the help of graphical illustrations.